2002
DOI: 10.1038/sj.hdy.6800122
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a mitochondrial lineage originating from the Arabian peninsula in the Madagascar house mouse (Mus musculus)

Abstract: Various subspecies of the house mouse (Mus musculus sensu lato) are known to have contributed to its worldwide expansion. However, the origin of mice on some larger islands such as Madagascar has remained unknown, with several sources being possible. In order to classify the Malagasy house mouse, individuals were trapped in 13 different localities distributed throughout the island. For 33 individuals the control region (D-Loop) of the mitochondrial DNA was partially sequenced and 21 males were typed for a Zfy-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
58
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 101 publications
(67 citation statements)
references
References 22 publications
8
58
1
Order By: Relevance
“…MOL, which carries a MUS/CAS composite genome has, as expected, an intermediate position in the tree. However, the NOR tree highlights a discrepancy with previous studies in the position of GEN by way of considering it either as a sister taxon of DOM (Duplantier et al, 2002;Rajabi-Maham et al, 2008), or as closely related to CAS (Bonhomme et al, 2007). This apparent conflict with published data may stem from the genomic compartments analyzed (mitochondrial vs nuclear markers), and requires further analyses with increased sample sizes to be resolved.…”
Section: Discussioncontrasting
confidence: 51%
See 3 more Smart Citations
“…MOL, which carries a MUS/CAS composite genome has, as expected, an intermediate position in the tree. However, the NOR tree highlights a discrepancy with previous studies in the position of GEN by way of considering it either as a sister taxon of DOM (Duplantier et al, 2002;Rajabi-Maham et al, 2008), or as closely related to CAS (Bonhomme et al, 2007). This apparent conflict with published data may stem from the genomic compartments analyzed (mitochondrial vs nuclear markers), and requires further analyses with increased sample sizes to be resolved.…”
Section: Discussioncontrasting
confidence: 51%
“…The subspecific assignation of the studied specimens was determined from published molecular analyses of these individuals (mitochondrial and nuclear sequences; Duplantier et al, 2002;Auffray et al, 2003;Bonhomme et al, 2007). These studies revealed that the mouse from Madagascar had a mosaic genome: while it clearly harbored a distinct mitochondrial genome attributed to GEN (Prager et al, 1998;Duplantier et al, 2002), nuclear markers indicated an affinity with CAS (Bonhomme et al, 2007). Where possible, the samples were pooled by geographic origin; given the extensive data for DOM, the specimens were grouped into three regional clusters: the Mediterranean Basin, including southern Europe (S), northern Europe (N) and the Atlantic Coast (A).…”
Section: Mouse Samplesmentioning
confidence: 99%
See 2 more Smart Citations
“…The synlophe was studied following the method of DuretteDesset (1985) and for the nomenclature of the axis of INTRODUCTION T wo previous articles (Durette-Desset et al, 2002a, b) dealt with the trichostrongylid fauna of taxonomical analysis of endemic rodents from Madagascar namely the Nesomyinae with the genera Nesomys Peters, 1870 and Eliurus Milne-Edwards, 1885. The present study describes a new species belonging to the genus Heligmonoides Baylis, 1928, parasitic in Mus musculus (Muridae), a non-native rodent which colonized Madagascar probably from the Arabian Peninsula (Duplantier et al, 2002). A new definition and a dichotomous key of this genus are provided with comments of its host-spectrum and biogeographical distribution.…”
mentioning
confidence: 99%